A Methodology to Consider Explicitly Emissions in Dynamic User Equilibrium Assignment - Silgu, Mehmet Ali; Erdaği, İsmet Göksad; Hülagu, Selin; Akti, Sercan; Akova, Hazal; Akyol, Görkem; Göncü, Sadullah; Göksu, Gökhan; Çelikoğlu, Hilmi Berk (Springer, 2022)
This work presents a methodology to obtain Dynamic User Equilibrium (DUE) over a road network considering the exhausted gas effect of motorized traffic. On purpose, three emission models are integrated to the traffic simulator AIMSUN, and an entire modeling structure is proposed. The proposed methodology is tested on both a hypothetical test network and a real-world network in Istanbul, Turkey. With the use of dynamic traffic assignment components of AIMSUN, emissions are incorporated into dynamic cost functions. Furthermore, link travel times are considered in the dynamic cost functions in conjunction with emissions. The DUE condition is converged according to dynamic cost functions. Results with the employment of different emission models on a real road network are compared and discussed.
Keywords: Dynamic Traffic Assignment; Vehicular Emissions; Traffic Simulation; Optimization